Hybrid warfare and the legal domain - Munoz Mosquera, Andres B. (Terrorism and political violence, 2019)
This short essay aims at shedding some light on the use of lawfare as an emerging domain of full spectrum warfare which can either be used in its own right to achieve its own strategic objectives or as an enabler within the context of influencing the adversary in connection with well-planned Info-Ops and Stratcom operations. The authors conclude that considering the law as a domain, the use of lawfare is an “Offset Strategy,” which will provide a considerable competitive advantage in the proper offensive and defensive applicability of law which will prevent potential adversaries to abuse the rule of law to achieve their own strategic objectives.